Traditional uses and pharmacological activities of Tetracera alnifolia (Wild) Drake - Camara, Aboubacar Kadiatou; Elhadj Saidou Balde; Mamadou Saliou Telly Diallo; Camara, Mohamed Kerfalla; Tanou Valdez Bah; Conde, Mamoudou; Soumah, Aboubacar; Tietjen, Ian; Balde, Aliou Mamadou (bioRxiv, 2024)
Ethnopharmacological relevance: Tetracera alnifolia (Wild) Drake, is well used in traditional Guinean medicine for the treatment of infectious skin diseases. The present aim was to contribute to the valorization of Tetracera alnifolia leaves, focused on ethnomedical, biological and phytochemical investigations. Materials and methods: we conducted an ethnomedical survey across several markets of the city of Conakry to identify 39 healers. Chloroform, methanol, dichloromethane, and aqueous extracts were tested for activities against protozoa, bacteria, fungi, HIV, and SARS-CoV-2. Results: the traditional healers indicated that T. alnifolia is used in the treatment of more than 15 pathologies including Fassa (marasmus/malnutrition), Soukhou kouye (white discharge in women), and Temou bankhi (sexual weakness in men). Leaves were the most used part. The modes of preparation included decoction and powder. Data from biological activities identicatied good activities of the methanolic extract against Leishmania infantum (MIC = 8.11 μg / ml) and a moderate activity on Trypanosoma brucei (MIC = 28.15 μg / ml) and Staphylococcus aureus (MIC = 29.91 μg/ ml), while dichloromethane extracts acted on live SARS-CoV-2 replication with up to 53.4% inhibition at 50 μg/mL. Conclusion: these results explain at least in part the traditional use of T. alnifoliaCompeting Interest StatementThe authors have declared no competing interest.